2013
DOI: 10.6113/jpe.2013.13.4.729
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Insulated-gate Bipolar Transistor Operating Temperature: Simulation and Experiment

Abstract: Knowledge of a power semiconductor's operating temperature is important in circuit design and converter control. Designing appropriate circuitry that does not affect regular circuit operation during virtual junction temperature measurement at actual operating conditions is a demanding task for engineers. The proposed method enables virtual junction temperature estimation with a dedicated modified gate driver circuit based on real-time measurement of a semiconductor's quasi-threshold voltage. A simulation was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Several studies evaluate the variations of the threshold voltages in IGBTs [28,29]. In [29], the effect of temperature on the threshold v Ge value was evaluated using different device manufacturers.…”
Section: The Closed-loop Gd Tuning and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies evaluate the variations of the threshold voltages in IGBTs [28,29]. In [29], the effect of temperature on the threshold v Ge value was evaluated using different device manufacturers.…”
Section: The Closed-loop Gd Tuning and Experimental Resultsmentioning
confidence: 99%
“…Several studies evaluate the variations of the threshold voltages in IGBTs [28,29]. In [29], the effect of temperature on the threshold v Ge value was evaluated using different device manufacturers. The results showed that the threshold voltage in different IGBTs was reduced up to 1 V by increasing the temperature from 25 • C to 120 • C. It is a key point that the increase of temperature has a negative effect on the v Ge(th) value.…”
Section: The Closed-loop Gd Tuning and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat generated by the high-power semiconductor device will cause the temperature rise of the chip. If there are no appropriate cooling measures, the working temperature of the chip will exceed the allowable maximum temperature, which will lead to deterioration or even damage of the device performance [1]. It has been shown that for every 10 • C increase in the temperature of a semiconductor chip, the reliability of the chip is reduced by half.…”
Section: Introductionmentioning
confidence: 99%
“…To realize the -method during inverter operation a switching sequence with attached measurement phase could be used [20,21], but this also results in an interruption of the motor current and deteriorates the system properties. In [22,23] the temperature sensitive quasi-threshold voltage is used for junction temperature measurement. Thereby the induced voltage across the parasitic inductance between the power emitter and an auxiliary emitter is used to trigger the measurement of the gate emitter voltage.…”
Section: Igbt Driver With Measurementmentioning
confidence: 99%